Whole-Genome/Exome Sequencing Uncovers Mutations and Copy Number Variations in Primary Diffuse Large B-Cell Lymphoma of the Central Nervous System - Zhu, Qiong; Wang, Jianchao; Zhang, Wenfang; Zhu, Weifeng; Wu, Zaizeng; Chen, Yanping; Chen, Musheng; Zheng, Limei; Tang, Jianqing; Zhang, Sheng; Wang, Di; Wang, Xingfu; et al. (Frontiers in Genetics, 2022)
Background/objective: Identification of key genetic alterations is of importance in the targeted therapies of primary central nervous system lymphoma (PCNSL). However, only a small number of studies have been carried out in PCNSL. In this study, we further described the genetic mutations and copy number variations (CNVs) in PCNSL patients using whole-genome/exome sequencing (WGS/WES), as well as revealed their associations with patients’ clinicopathological features and prognosis. Methods: Tumor specimens from 38 patients with primary diffuse large B-cell lymphoma of the central nervous system (CNS DLBCL) were enrolled to WGS (n=24) or WES (n=14). The CNVs and mutations of 24 samples (WGS) and 38 samples (WGS/WES) were characterized, respectively. The association between CNVs and mutations with the overall survival rates of PCNSL patients were also evaluated. Results: The most common mutations were identified in IGLL5 (68%), PIM1 (63%), MYD88 (55%), CD79B (42%), BTG2 (39%), PCLO (39%), KMT2D (34%), BTG1 (29%) genes. Among the mutated genes, EP300, ETV6 and HIST1H1E mutations were exclusively detected in the elderly, while DUSP2 mutations were associated with the immune microenvironment indicators. In addition, KMT2D mutation was associated with poor prognosis. In addition, 488 CNVs including 91 gains and 397 deletions were observed across 24 samples from WGS results. Notably, 1q31.3 amplification was closely associated with the poor prognosis of PCNSL patients. Conclusion: This study further characterizes the genomic landscape of primary CNS DLBCL using WGS/WES, which provides insight understanding the pathogenesis of PCNSL and foster new ideas for the targeted treatment of PCNSL.